The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3390/molecules25173879
|View full text |Cite
|
Sign up to set email alerts
|

Ethnopharmacology of Fruit Plants: A Literature Review on the Toxicological, Phytochemical, Cultural Aspects, and a Mechanistic Approach to the Pharmacological Effects of Four Widely Used Species

Abstract: Fruit plants have been widely used by the population as a source of food, income and in the treatment of various diseases due to their nutritional and pharmacological properties. The aim of this study was to review information from the most current research about the phytochemical composition, biological and toxicological properties of four fruit species widely used by the world population in order to support the safe medicinal use of these species and encourage further studies on their therapeutic properties.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 186 publications
(180 reference statements)
0
10
0
Order By: Relevance
“…Most Moraceae species have not yet been chemically studied [40] . However, the compounds with the highest number of occurrences in the family are coumarins, especially furocoumarins, which are used to treat not only vitiligo but also other skin disorders, such as systemic lupus erythematosus and mycoses [41] . Moreover, coumarins show several biological activities, such as photosensitizer, antimicrobial, anticoagulant, vasodilatory, sedative, and analgesic activities [40] .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Most Moraceae species have not yet been chemically studied [40] . However, the compounds with the highest number of occurrences in the family are coumarins, especially furocoumarins, which are used to treat not only vitiligo but also other skin disorders, such as systemic lupus erythematosus and mycoses [41] . Moreover, coumarins show several biological activities, such as photosensitizer, antimicrobial, anticoagulant, vasodilatory, sedative, and analgesic activities [40] .…”
Section: Resultsmentioning
confidence: 99%
“…Cerrado fruits are considered a source of bioactive substances, mainly phenolic compounds, probably because of exposure to water stress, high ultraviolet radiation, herbivore attacks and fungal infections, which are common conditions in Cerrado plants [46] . These compounds show therapeutic properties with anti‐inflammatory, antimicrobial, and antioxidant potential, among others [41] . Thus, to obtain a higher extraction yield of phenolic compounds and consequently greater antioxidant activity, the hydroethanolic extract of the fruits of inharé was used for the tests of antioxidant activity.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The comprehensive work of De Carvalho and collaborators explored the phytochemical composition, biological and toxicological properties of four fruit species, i.e., Talisia esculenta, Brosimum gaudichaudii, Genipa americana, and Bromelia antiacantha [ 2 ]. They reported that these plants demonstrated anti-inflammatory, antitumor, and photosensitizing properties, in addition to providing key molecules with pharmacological and healthy activity.…”
mentioning
confidence: 99%